2016
DOI: 10.1103/physreva.94.013429
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond delay of xenon4dphotoionization at the giant resonance and Cooper minimum

Abstract: A Kohn-Sham time-dependent local-density-functional scheme is utilized to predict attosecond time delays of xenon 4d photoionization that involves the 4d giant dipole resonance and Cooper minimum. The fundamental effect of electron correlations to uniquely determine the delay at both regions is demonstrated. In particular, for the giant dipole resonance, the delay underpins strong collective effect, emulating the recent prediction at C60 giant plasmon resonance [T. Barillot et al, Phys. Rev. A 91, 033413 (201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Strong negative delays near the resonance indicate accelerated emissions of the electron for both Xe and I. This corroborates to the general expectation of a collective-type resonance environment in which electrons feel transient repulsion as the emission process becomes favored [3]. In contrast, an opposite temporal trend is displayed near the CM region where the delays appear positive.…”
Section: Related Contentsupporting
confidence: 67%
“…Strong negative delays near the resonance indicate accelerated emissions of the electron for both Xe and I. This corroborates to the general expectation of a collective-type resonance environment in which electrons feel transient repulsion as the emission process becomes favored [3]. In contrast, an opposite temporal trend is displayed near the CM region where the delays appear positive.…”
Section: Related Contentsupporting
confidence: 67%
“…While the time delays for Ne and Ar( s 3 ) increase rather smoothly as a function of XUV frequency, a pronounced minimum appears around the Cooper minimum for Ar( p 3 ). The minimum arises from the Wigner-Smith time delay and is related to the change of sign in the dipole matrix element [43][44][45][46][47].…”
Section: Modeling Chirp Effect On Streaking Time Delaymentioning
confidence: 99%
“…Second, we report results of photoionization time-delay studies. Wigner-Eisenbud-Smith time delay [34][35][36], τ WES , is known to be affected strongly by correlation and relativistic interactions, especially in the region of Cooper minima [37][38][39][40][41][42][43][44]. A few photoionization time delay studies on atomic xenon have been reported [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Wigner-Eisenbud-Smith time delay [34][35][36], τ WES , is known to be affected strongly by correlation and relativistic interactions, especially in the region of Cooper minima [37][38][39][40][41][42][43][44]. A few photoionization time delay studies on atomic xenon have been reported [41][42][43][44][45]. Most recently, studies of the angular dependence of photoionization time delay of Xe 5s in the near threshold region, in the vicinity of the FCM have been examined theoretically [44].…”
Section: Introductionmentioning
confidence: 99%